The Influence of Literature on Society (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This study examines the influence of literature on society, highlighting its role in shaping cultural values, fostering critical thinking, and promoting empathy. Addressing the gap in understanding literature’s societal impact, it employs qualitative analysis of key texts. Findings reveal literature's profound ability to inspire change, emphasizing its relevance in contemporary discourse. Literature serves as a profound tool that reflects and shapes society. It bridges generations, preserves cultural identity, and inspires change. This article explores the role of literature in fostering empathy, documenting history, and challenging societal norms. Additionally, it examines the unique influences of literature in English and Uzbek societies, highlighting cultural and historical perspectives.